The evolving plasticity of coagulation protease-dependent cytoprotective signalling - Shahzad, K.; Isermann, B. (Hämostaseologie, 2011)
Coagulation proteases control cellular homeostasis beyond haemostasis. While the role of coagulation proteases in regulating vascular healing and thrombosis is well established, the mechanism underlying the receptor-dependent regulation of cellular function remain incompletely understood. In particular, the opposing effects of the protease-activated receptor 1 (PAR-1), dependent on the activating proteases thrombin or activated protein C generated a conundrum researchers only recently have begun to decipher. The net-effect (cellular perturbation vs. cellular protection) depends on co-receptors involved, the concentration of the activating protease, the temporal context of receptor activation, and a dynamic process of receptor rearrangement upon receptor activation. The latter scenario recruits receptors to a cytoprotective signalling pathways. Recent insights into these mechanisms are summarized in this article.
Keywords: Protease activated receptor; protein C; thrombin; cytoprotection; biased signalling